Distortion behaviour analysis of additively manufactured inconel 718 using numerical computation / Azri Rahimi Abd Rahman ... [et al.] - Abd Rahman, Azri Rahimi; Muhammad, Nor Asiah; Mat, Muhd Faiz; Manurung, Yupiter Hp; Adenan, Mohd Shahriman; Busari, Yusuf Olanrewaju; Prajadhiana, Keval Priapratama; Ginta, Turnad Lenggo; -, Triyono (UiTM Press, 2025)
Metal Additive Manufacturing (MAM) is a rapidly growing technology that has the potential to revolutionize the manufacturing industry. One of the current MAM processes is direct energy deposition (DED), which uses layer-by-layer deposition to design for part consolidation and minimize materials wastage. However, repeated heating and cooling of the DED process often exhibit distortions in AM components, leading to premature failure. The study presents the numerical computation analysis of the thermally induced distortion of additively manufactured Inconel 718 on SS316 substrate utilizing the DED process with the help of numerical computation software Simufact Welding. The geometry design of the Inconel 718 component and SS316 substrate is designed to establish a deeper understanding of the LMD process’s distortion behaviour. The simulation results show that the distortions increase with the number of layers, and the distortion rate varies along the deposition height. Deformation of the substrate at nodes S3 and S5 increased linearly in each of the deposited layers, but the rate decreased at nodes S1 and S2 during the last four layers suggesting temperature uniformity between the substrate and the deposited material.